(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article examines the ecological, economic, and agronomic consequences of wind erosion processes in Uzbekistan and the measures for diagnosing and preventing them based on mathematical modeling. In particular, the dynamics of dust storm processes caused by anthropogenic factors in the Aral Sea region, their regional impact, the degradation of soil fertility, and their adverse effects on agricultural production are scientifically analyzed. The main goal of the study is to develop a comprehensive model for managing wind erosion and automated monitoring systems.